Historical climatic extremes as indicators for typical scenarios of Holocene climatic periods in the Pampean plain - Iriondo, Martin Horacio (2009)
The Holocene has been marked by two different climatic periods in the Pampas, one (8.5-3.5 kyr B.P.), characterized by temperatures and precipitation higher than today and the other (3.5-1.4 kyr B.P.) semiarid, generating parabolic dunes. The humid period produced intense pedogenesis down to 40° lat. S and a mobilization of iron oxides to 30° lat. S, which means tropical climate with temperatures above 20 °C and precipitation higher than 2000 mm/yr. Sand deflation and development of parabolic dunes occur under climates with 300-400 mm/yr. This contribution is based on geological and physical proxies. Typical weather scenarios of those climates are sporadically reproduced today during extremely humid or dry periods. On that basis, meteorological parameters of years beyond the thresholds of 2000 and 400 mm/yr were processed. Dry periods were characterized by a large thermal amplitude, frosts and stronger winds, reproducing the continental anticyclonic circulation of the Late Holocene. Humid extremes were warmer than normal (lower thermal amplitude), with rains produced by local convection processes. Typical scenarios with precipitation above 2000 mm/yr are: 21 °C mean temperature (ca. 1 °C higher than the Present record); 27 °C maximal annual temperatures; 16 °C minimal annual temperatures (more than 1 °C higher than the Present); as a consequence, thermal amplitude was smaller than today, virtually without frosts. Characteristic parameters of the Late Holocene were: mean annual precipitation ca. 350 mm/yr; 15 °C mean temperature; 22 °C maximal annual temperatures; 8 °C minimal annual temperatures, showing significative shifts in the dry season (lower than normal); monthly maximal and mean temperatures higher than today. The result is a thermal amplitude larger than today. Probably, higher quantity of frosts per year, stronger winds and lower relative air humidity in comparison with the humid climate extreme, complete the scenario.